Identifying Balance and Fall Risk in Community-Dwelling Older Women: The Effect of Executive Function on Postural Control - Muir-Hunter, Susan W. (University of Toronto Press Incorporated, 2014)
Purpose: The mechanisms linking cognition, balance function, and fall risk among older adults are not fully understood. An evaluation of the effect of cognition on balance tests commonly used in clinical practice to assess community-dwelling older adults could enhance the identification of at-risk individuals. The study aimed to determine (1) the association between cognition and clinical tests of balance and (2) the relationship between executive function (EF) and balance under single- and dual-task testing. Methods: Participants (24 women, mean age of 76.18 [SD 16.45] years) completed six clinical balance tests, four cognitive tests, and two measures of physical function. Results: Poor balance function was associated with poor performance on cognitive testing of EF. In addition, the association with EF was strongest under the dual-task timed up-and-go (TUG) test and the Fullerton Advanced Balance Scale. Measures of global cognition were associated only with the dual-task performance of the TUG. Postural sway measured with the Standing Balance Test, under single- or dual-task test conditions, was not associated with cognition. Conclusions: Decreased EF was associated with worse performance on functional measures of balance. The relationship between EF and balance was more pronounced with dual-task testing using a complex cognitive task combined with the TUG.